2023
DOI: 10.3389/fphar.2023.1170243
|View full text |Cite
|
Sign up to set email alerts
|

Chrysin ameliorates synovitis and fibrosis of osteoarthritic fibroblast-like synoviocytes in rats through PERK/TXNIP/NLRP3 signaling

Abstract: Objective: Synovitis and fibrosis are common pathological features of knee osteoarthritis (KOA). The interaction of synovitis and fibrosis can promote KOA progression. Chrysin (CHR), a natural flavonoid, may treat inflammation and prevent fibrosis. However, the effect and mechanism of CHR in KOA synovitis and fibrosis remains unclear.Methods: The KOA model was established in male SD rats by anterior cruciate ligament transection (ACLT), and histological analysis was used to evaluate synovitis and fibrosis. IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…This 5,7-dihydroxyflavone was characterized by antioxidant, antitumor, anti-hypercholesterolemic and anti-inflammatory activities ( Bae et al, 2011 ; Brechbuhl et al, 2012 ; Ali et al, 2014b ; Anandhi et al, 2014 ; Samarghandian et al, 2016 ; Phan et al, 2021 ). Our data are in line with other research that identified CHR-mediated inhibition of pro-fibrotic pathways in rat myocardial injury, renal fibrosis and osteoarthritis, by reducing TGF-β1/Smad3, p38, Erk1/2, MMP2 and PERK/TXNIP/NLRP3 signalling ( Rani et al, 2015 ; Nagavally et al, 2021 ; Ding et al, 2023 ). Additionally, by using a different pharmacological approach, we demonstrated that TGF-β/Smad pathway can be reduced in human retinal pigment epithelial cells exposed to high glucose by using calixarene OTX008, a selective inhibitor Gal-1 ( Trotta et al, 2022 ).…”
Section: Discussionsupporting
confidence: 93%
“…This 5,7-dihydroxyflavone was characterized by antioxidant, antitumor, anti-hypercholesterolemic and anti-inflammatory activities ( Bae et al, 2011 ; Brechbuhl et al, 2012 ; Ali et al, 2014b ; Anandhi et al, 2014 ; Samarghandian et al, 2016 ; Phan et al, 2021 ). Our data are in line with other research that identified CHR-mediated inhibition of pro-fibrotic pathways in rat myocardial injury, renal fibrosis and osteoarthritis, by reducing TGF-β1/Smad3, p38, Erk1/2, MMP2 and PERK/TXNIP/NLRP3 signalling ( Rani et al, 2015 ; Nagavally et al, 2021 ; Ding et al, 2023 ). Additionally, by using a different pharmacological approach, we demonstrated that TGF-β/Smad pathway can be reduced in human retinal pigment epithelial cells exposed to high glucose by using calixarene OTX008, a selective inhibitor Gal-1 ( Trotta et al, 2022 ).…”
Section: Discussionsupporting
confidence: 93%
“…Inflammation is prevented by CH treatment because it decreased lipid metabolism by inhibiting AMPK and inflammasome activation by blocking NLRP3 [ 50 ]. CH may treat inflammation and prevent fibrosis by decreasing the inflammatory response and fibrosis induced by TGF-β1 in synovial fibroblasts (SFs) via inhibiting thioredoxin-interacting protein (TXNIP)-NLRP3 interactions in TGF-β-induced SFs [ 51 ]. CH reduces hypercholesterolemia-mediated atherosclerosis via modulating the inflammatory genes expression including TNF-α , toll-like receptors ( TLR4 ), IL-17 , and NLRP3 in the intestine and aorta compared with hypercholesterolemia control rats [ 52 ].…”
Section: Anti-inflammatory Mechanismsmentioning
confidence: 99%
“…Flavones are obtained by dehydrogenation of flavanones, and they are the most representative class of flavonoids. We have found fifteen manuscripts on 11 molecules: acacetin, apigenin, chrysin, diosmetin (DIOS; 3′,5,7-trihydroxy-4′-methoxy flavone), luteolin, nepetin, orientin, oroxylin-A, rhoifolin (ROF), scutellarin, and velutin [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. Acacetin (5,7-dihydroxy-4′-methoxyflavone) is the major bioactive component of the traditional Chinese medicine “Snow lotus” ( Saussurea involucrata ) and is present in some plants, such as Robinia pseudoacacia , Turnera diffusa, and Betula pendula .…”
Section: Flavonoid Classes and Activities On Oamentioning
confidence: 99%
“…Chrysin also exhibits some in vivo biological activities, as demonstrated in a rat knee MIA-induced OA model. By experiments of quantitative real-time polymerase chain reaction (qRT-PCR), Western blotting, enzyme-linked immunosorbent assay (ELISA), and immunofluorescence, the authors demonstrated that chrysin decreased inflammation status, reduced some other OA endpoints, inhibited NLRP-3 inflammasome activation, and ultimately alleviated the synovitis [ 55 ]. More recently, some authors, through in vivo and in vitro studies, while confirming these data, have added the important detail that chrysin also reduced the inflammatory response induced by TGF-β1 and fibrosis in FLSs with the conclusion that it can improve synovitis and fibrosis in knee OA by performing, among others, this specific mechanism of action [ 56 ].…”
Section: Flavonoid Classes and Activities On Oamentioning
confidence: 99%